Examining the associations between mental health, life balance, work-method autonomy, and perceived boundary control among postdoctoral fellows - Lo, Brian K.; Park, In Young; Choung, David; McTernan, Melissa; Sibley, Erin; Davison, Kirsten K. (Frontiers in Psychology, 2024)
High mental health risks and life imbalance among postdoctoral fellows (postdocs) are persistent concerns in academia. However, little is known about the relationship between these two subjects and whether autonomy at work is linked to life balance among postdocs. Online survey responses from 117 postdocs (59% women; 49% non-Hispanic white) were assessed using multiple linear regression analysis to examine whether the work-method autonomy and perceived boundary control of postdocs were linked to life balance. Additionally, logistic regression analysis was used to examine whether postdocs who reported better life balance had lower risks of reporting mood disorder symptoms. We found that 39%, 27%, and 45% of postdocs reported anxiety, depressive, and anxiety-or-depressive disorder symptoms, respectively. Both work-method autonomy and perceived boundary control were positively associated with life balance [B = 0.40, 95% CI = [0.20–0.60]; B = 0.50, 95% CI = [0.32–0.67], respectively]. Postdocs with greater life balance had decreased odds of reporting mood disorder symptoms [anxiety disorder symptoms: adjusted OR = 0.55, 95% CI = (0.37–0.82); depressive disorder symptoms: adjusted OR = 0.31, 95% CI = (0.18–0.55); anxiety-or-depressive disorder symptoms: adjusted OR = 0.42, 95% CI = (0.27–0.65)]. Postdocs' mental health appeared to be influenced by life balance, which may be enhanced by providing work-method autonomy and increasing perceived boundary control.